1986
DOI: 10.1002/jso.2930310107
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosarcoma of the transverse colon

Abstract: Colonic fibrosarcoma is extremely rare. This is a report of a patient with fibrosarcoma of the transverse colon, manifesting as an obstructive lesion with local perforation and abscess formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The existence of a fibrosarcoma in the colon is extremely rare. After a fibrosarcoma of the colon was first recognized in 1949, fibrosarcomas were associated with ulcerative colitis, which had generally been studied [ 1 , 2 , 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of a fibrosarcoma in the colon is extremely rare. After a fibrosarcoma of the colon was first recognized in 1949, fibrosarcomas were associated with ulcerative colitis, which had generally been studied [ 1 , 2 , 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a fibrosarcoma is most frequently observed in the early years of life and is extremely rare in adults. Review articles have reported only four cases involving a fibrosarcoma of the colon [ 1 , 2 , 3 , 4 ]. Here, we report our experience with a case of acute peritonitis caused by a fibrosarcoma of the transverse colon in an adult.…”
Section: Introductionmentioning
confidence: 99%
“…36 Fibrosarcoma originates mainly in the soft tissue of extremities and is uncommon in the retroperitoneum and gastrointestinal tract. 37,38 Rhabdomyosarcoma occurs predominantly in children. The genito-urinary tract is a common site of origin (21%), compared with the extremities (20%), parameningeal region (14%), head and neck (13%), and retroperitoneum (8%).…”
Section: Treatmentmentioning
confidence: 99%